Determinación de las principales plagas que afectan el cultivo de tomate de árbol (Cyphomandra betacea L.) en la comunidad de Yahuarcocha, cantón Ibarra Provincia de Imbabura, 2017 - Mena Gaibor, Fredy Marcel (2018)
SUMMARY The present research work was developed in order to identify, characterize and evaluate the pests of the “tomate de arbol” in the region of Yahuarcocha Imbabura. To achieve this, a literature review on "tomate de arbol” cultivation was initially carried out, the characteristics of the product, management conditions, local and international market and the pests associated with the product; Subsequently, several visits were made to the Yahuarcocha area in order to initially identify the tomato growers, to then conduct surveys of the total population, taking into account that it is a small number of people engaged in this work, no sampling was done. Within the surveys, the following points were mainly evaluated, regarding the tomato tree crop: crop surface, profitability, pest symptoms observed in the root and fruit, main factors associated with pests and the stage of cultivation in which greater inconveniences are observed.